The regulation of antiviral innate immunity through non-m6A RNA modifications - Shen, Shenghai; Zhang, Li-Sheng (Frontiers in Immunology, 2023)
The post-transcriptional RNA modifications impact the dynamic regulation of gene expression in diverse biological and physiological processes. RNA modifications also play an indispensable role in regulating innate immune responses against virus infection in mammals. Meanwhile, the viral RNAs can be deposited with RNA modifications to interfere with the host immune responses. The N6-methyladenosine (m6A) has boosted the recent emergence of RNA epigenetics, due to its high abundance and a transcriptome-wide widespread distribution in mammalian cells, proven to impact antiviral innate immunity. However, the other types of RNA modifications are also involved in regulating antiviral responses, and the functional roles of these non-m6A modifications have not been comprehensively summarized. In this Review, we conclude the regulatory roles of 2'-O-methylation (Nm), 5-methylcytidine (m5C), adenosine-inosine editing (A-to-I editing), pseudouridine (Ψ), N1-methyladenosine (m1A), N7-methylguanosine (m7G), N6,2’-O-dimethyladenosine (m6Am), and N4-acetylcytidine (ac4C) in antiviral innate immunity. We provide a systematic introduction to the biogenesis and functions of these non-m6A RNA modifications in viral RNA, host RNA, and during virus-host interactions, emphasizing the biological functions of RNA modification regulators in antiviral responses. Furthermore, we discussed the recent research progress in the development of antiviral drugs through non-m6A RNA modifications. Collectively, this Review conveys knowledge and inspiration to researchers in multiple disciplines, highlighting the challenges and future directions in RNA epitranscriptome, immunology, and virology.